Research of the possibility of application of vector quantisation method for effective process control of rocks disintegration by rotary drilling - Lesso, I; Flegner, P; Sujansky, M; Spak, E (Metalurgija, 2010)
Preliminary Note - Prethodno pripocenje The subject of the paper is investigation of the properties of concurrent vibro-acoustic signal in the process of rock massif separation with the method of rotary drilling. The aim is to investigate the possibilities of using this signal as an integrating information source for the purposes of identification of the process of separation from the viewpoint of efficiency of the set mode (pressure, revolutions, indentor) under current geotechnical conditions. Investigated is the possibility of recognition of the state of the process based on the method of vector quantisation.